FKEE Form Validity Verifications using Steganography Technique; Comparison Between Least Significant Bit (LSB) and Single Value Decomposition (SVD) - Ali Sabri, Nur Syafiqah; Ali, Siti Hajar Aminah (Evolution in Electrical and Electronic Engineering, 2022)
Faculty of Electrical and Electronic Engineering (FKEE) UTHM has used the new way of processing crucial forms with student and instructor signatures to validate such document. To validate FKEE forms and safeguard academician signatures, a system is presented. This system has two primary menus: (1) the generation of signature images with embedded matric numbers and excel files, and (2) the administration staff's form validity verification. Academicians must log in and select "Embedding" This menu requires the academician's signature and student's matric number. The technology generates an Excel file with steganography data. The academician staff will then share the signed form and excel file with the student. To validate the form, administration staff must select "Extraction" to decode the Excel file and extract the student's matric number. This project concludes that Least Significant Bit (LSB) can validate documents by extracting matric numbers. Next, it has 100% accuracy by testing the system with 3 different signature images. Single Value Decomposition (SVD) fails because it can only embed the hidden watermark but not extract the matric number-based watermark to its original image. This project's goals are finally met.